Ionospheric Storms over Kazakhstan Based on Integrated Electronic Content Data - Mukasheva, S.N.; Соколова, О.И. (Recent Contributions to Physics, 2022)
This paper presents the results of statistical analysis of ionospheric disturbances in the integral electronic content, NF, during the period of registration of the Faraday effect at the point of Almaty [43,20N; 76,90E] when receiving signals from the ETS-II satellite (Engineering Test Satellite Type-II), located in geostationary orbit [00N; 1300E], the radio beacon of which operated at a frequency of 136,112 MHz. The analysis of the classification characteristics of each specific event showed that perturbations in the integral electronic content can occur both with a positive (35 cases out of 83) and with a negative sign in (37 cases out of 83), as well as with a change of phases (with a change of sign) in the course of the perturbation. According to the start time, ionospheric disturbances tend to occur more often in the evening and at night, with a greater probability at 17 LT -22 LT. During the year, NF disturbances occur most frequently in the months of November, December, January, February, and March. A decrease in the number of ionospheric disturbances is detected based on the data on the integral electron content of the ionosphere during the period of high solar activity. The «disappearance» of storms in the integral electron content occurs approximately at F10. 7 > 180, which is probably due to the «saturation» effect in the ionosphere.